Private Savings and COVID-19 in Sub-Saharan Africa - Loko, Boileau (IMF Working Papers; Working Paper, 2022)
The paper reexamines the main private savings determinants in Sub-Saharan Africa (SSA), followed by an analysis of the COVID-19 pandemic impact on private savings in SSA and other country groupings. Using an unbalanced panel data from 1983-2021 for 31 SSA economies, the paper finds that real per capita economic growth remains a key historical determinant of private savings in the region. In contrast with other regions, private saving rates have not increased during COVID-19 in SSA. Instead, COVID-19 deaths in our estimations are significantly associated with a decline in private savings in SSA. Robustness checks and a descriptive analysis of household surveys during the pandemic corroborate those results.